Multicast/broadcast network convergence in next generation mobile networks - Santos, Justino (2008)
The 3GPP Multimedia Broadcast Multicast Service (MBMS) aims to introduce group communications into the 3G networks. One of the current key challenges is how to evolve these incipient features towards the "beyond 3G vision" of a converged global network where multimedia content can be delivered over one or more selected broadcast transport bearers. This paper presents potential multicast/broadcast technologies convergence and discusses the issues and challenges in moving towards this next generation network vision from the viewpoint of evolving MBMS. (C) 2007 Elsevier B.V. All rights reserved.